2018
DOI: 10.1097/der.0000000000000409
|View full text |Cite
|
Sign up to set email alerts
|

Effective Use of Dupilumab in Managing Systemic Allergic Contact Dermatitis

Abstract: Allergic contact dermatitis to metals has become increasingly recognized in patients with endovascular implants. The ACD can lead to in-stent restenosis as well as a prominent eczematous reaction overlying the implant, often necessitating its removal. We present a case of refractory allergic contact dermatitis to nickel in a 44-year-old man with numerous endovascular stents and vascular clips. He developed numerous adverse effects of systemic therapy to manage his symptoms including recurrent infections leadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 11 publications
0
23
0
1
Order By: Relevance
“…These cytokines are thought to play a central role in the pathogenesis of AD. Dupilumab has been approved recently, after it was shown to be a successful treatment for AD in several phase III clinical trials . These trials showed improvement of disease severity, itch, sleep disturbance, anxiety, depression and quality of life with dupilumab as monotherapy or in combination with TCSs .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These cytokines are thought to play a central role in the pathogenesis of AD. Dupilumab has been approved recently, after it was shown to be a successful treatment for AD in several phase III clinical trials . These trials showed improvement of disease severity, itch, sleep disturbance, anxiety, depression and quality of life with dupilumab as monotherapy or in combination with TCSs .…”
mentioning
confidence: 99%
“…Dupilumab has been approved recently, after it was shown to be a successful treatment for AD in several phase III clinical trials. [11][12][13] These trials showed improvement of disease severity, itch, sleep disturbance, anxiety, depression and quality of life with dupilumab as monotherapy or in combination with TCSs. 3 The most frequently observed side-effects were conjunctivitis, herpes infections and injection-site reactions.…”
mentioning
confidence: 99%
“…However, in a study of chromium‐induced contact dermatitis, chromium‐exposed workers with contact dermatitis had high T‐IgE levels and eosinophilic counts 11 . Eosinophilia and elevated T‐IgE levels are also reported in several cases of SCD 12,13 . Her eosinophil count returned to normal within 3 weeks after the pacemaker was removed.…”
Section: Discussionmentioning
confidence: 87%
“…She remained nearly clear while receiving dupilumab, and could continue her work. Joshi and Khan reported a case of refractory ACD caused by nickel in a patient after the placement of vascular stents because of an arterial popliteal thrombus . He had no personal or family history of AD.…”
Section: Discussionmentioning
confidence: 99%